PENGARUH BEBAN KERJA DAN PENGEMBANGAN KARIR TERHADAP KEPUASAN KERJA KARYAWAN PADA PT BANK NEGARA INDONESIA KANTOR CABANG UTAMA FATMAWATI - Kamsidik, Kamsidik; Irmal, Irmal; Kartika, Yunita (Yayasan Education and Social Center, 2025)
The purpose of this study was to determine the effect of Workload and Work Discipline on employee performance at PT. Bank Negara Indonesia, Fatmawati Main Branch Office, both partially and simultaneously. The method used was the Quantitative Associative method. The population in this study was all employees of PT. Bank Negara Indonesia, Fatmawati Main Branch Office. The sampling technique used was the saturated sampling method with a sample of 62 respondents. Data analysis methods used simple linear regression, multiple linear regression, correlation coefficient, coefficient of determination, partial t-test, and F-test. The results of this study indicate a positive and significant effect of Workload on employee performance at PT. Bank Negara Indonesia, Fatmawati Main Branch Office. This is evidenced by the simple linear regression equation Y = 16.016 + 0.400X1. The correlation value is 0.662 (strong). The coefficient of determination is 43.8%. The calculated t value of 6.842 is greater than the t-table value of 2.000, with a significance level of 0.000 < 0.05. Work Discipline has a positive and significant influence on employee performance at PT. Bank Negara Indonesia, Fatmawati Main Branch Office. This can be proven by the simple linear regression equation Y = 14.083 + 0.440X2. The correlation value is 0.691 (strong). The coefficient of determination is 47.7%. The calculated t value is 7.403 > t table 1.988 with a significance level of 0.000 < 0.05. Simultaneously, there is a positive and significant influence of Workload and Work Discipline on employee performance at PT. Bank Negara Indonesia, Fatmawati Main Branch Office. This can be proven by the multiple linear regression equation Y = 11.130 + 0.229X1 + 0.290X2. The correlation value is 0.751 (strong). The coefficient of determination is 56.5%. The calculated F value is 38.256 > F table 4.00 with a significance level of 0.000 < 0.05.